Exploring the Performance of Banking Industry in the UK During Current Financial Crisis - Xu, C (2010)
UK banks underwent a series of damage during this current crisis. This study explores the performance of UK banks in this ongoing crisis. Meanwhile, a pooled OLS regression is applied to investigate the effect of internal and external determinants on performance of 43 UK- own banks that cover the period 2005-2009. The financial data used in the empirical work are obtained mainly from the Bankscope Database of Bureau van Dijk’s company. The estimation results show that the return on assets (ROA) of UK banks decreased sharply from 1.01% in 2005 to -1.10% in 2009. Seven internal determinants are considered in this study, the results shows that all the internal determinants are affect the performance of UK banks significantly. Most of the internal determinants, with the exception of bank size, positively affect the performance of UK banks. It indicates that lack of liquidity, holding a relative low amount of capital and low credit risk are the main causes of poor performance for UK banks. The bank size affect bank performance negatively and significantly in this study, which indicate UK banks experience the scale inefficiency during the sample period. In this study, external determinants such as GDP growth and market structure are positive but statistically insignificant related to bank’s interest margins and profitability.